Analysis of perfluorinated compounds in human serum from the general population in Shanghai by liquid chromatography-tandem mass spectrometry (LC-MS/MS). (February 2017) - Wu, Minghong; Sun, Rui; Wang, Mingnan; Liang, Huanhuan; Ma, Sihan; Han, Tao; Xia, Xiaoyu; Ma, Jing; Tang, Liang; Sun, Yanfeng; Xu, Gang
Abstract: Perfluorinated compounds (PFCs) have potential health risk to human. In this paper, human serum samples collected from Jiading District, Shanghai aged from 23 to 87 years old (12 male and 33 female) were analyzed for 17 perfluorinated compounds (PFCs). A novel method for the elimination of background contamination of perfluorooctanoic acid (PFOA) generated from instrument by the modification of high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) has also been developed and validated. The limit of detection (LOD) for all monitored PFCs range from 0.02 to 0.18 ng mL −1 . The limit of quantitation (LOQ) for PFOS and PFOA was 2.23 and 1.60 ng mL −1, respectively, and for other PFCs it ranged from 0.04 to 0.88 ng mL −1 . Of the 17 PFCs analyzed in Shanghai serum, eleven were found. The dominating PFCs in all samples were perfluorooctanesulfonate (PFOS) and PFOA with a fraction of 49.5%, 34.2%, respectively. The median total concentration of each serum samples was 53.43 ng mL −1 with a range from <LOD to 99.37 ng mL −1 . The results indicate a high human exposure to PFCs in Shanghai region. Compared with other cities in China and some other countries, PFOA and PFDA concentrations in the serum of general population of Shanghai are highest. For all donors, no significant association between age and PFCs was found (p = 0.125–0.951) and no workplace significant correlation was found (p = 0.247–0.861). Since no signification is founded and PFCs exposure is prevalent, further investigation is needed to explore its source and potential health impact. These results will also provide significant background data of PFCs in Shanghai. Highlights: A novel method for the elimination of perfluorooctanoic acid (PFOA) background contamination from HPLC instrument was set up. A total of 11 perfluorinated compounds (PFCs) were found in all the human serum samples from Shanghai population. No significant relationship between age or workplace and PFCs concentration was found. PFOA and PFDA concentrations are the highest in the serum of general population of Shanghai.